CRISPR/Cas9 for potato functional genomics and breeding - Gonzalez, Matías Nicolás; Massa, Gabriela Alejandra; Andersson, Mariette; Storani, Leonardo; Olsson, Niklas; Decima Oneto, Cecilia Andrea; Hofvander, Per; Feingold, Sergio Enrique (Humana Press (Springer), 2024)
Cultivated potato (Solanum tuberosum L.) is one of the most important staple food crops worldwide. Its tetraploid and highly heterozygous nature pose a great challenge to its basic research and trait improvement through traditional mutagenesis and/or crossbreeding. The establishment of the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein 9 (Cas9) as a gene-editing tool has allowed the alteration of specific gene sequences and their concomitant gene function, providing powerful technology for potato gene functional analysis and improvement of elite cultivars. This technology relies on a short RNA molecule called single guide RNA (sgRNA) that directs the Cas9 nuclease to induce a site-specific double-stranded break (DSB). Further, repair of the DSB by the error-prone non-homologous end joining (NHEJ) mechanism, leads to the introduction of targeted mutations, which can be used to produce the loss of function of specific gene/s. In this chapter, we describe experimental procedures to apply the CRISPR/Cas9 technology for potato genome editing. First, we provide strategies for target selection and sgRNA design and describe a Golden Gate-based cloning system to obtain a sgRNA/Cas9-encoding binary vector. We also describe an optimized protocol for ribonucleoprotein complexes (RNP) assembly. The binary vector can be used for both Agrobacterium-mediated transformation and transient expression in potato protoplasts, while the RNP complexes are intended to obtain edited potato lines through protoplast transfection and plant regeneration. Finally, we describe procedures to identify the gene-edited potato lines. The methods described here are suitable for potato gene functional analysis and breeding.